2000
DOI: 10.1002/(sici)1096-9071(200005)61:1<37::aid-jmv6>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-free virion titer greatly differs between hepatitis C virus genotypes

Abstract: Hepatitis C virus (HCV) virions have been shown to be bound to antibodies in patients with chronic HCV infection. The sera from patients infected with genotype 1b HCV contained more antibody-free virions than those from patients with genotype 2a/2b HCV. When compared at the same levels of serum HCV RNA, free virion titers of genotype 2a/2b-infected patients were much lower than those of genotype 1b-infected patients, indicating that a larger fraction of HCV virions are bound to antibodies in the former than in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…This conclusion is strengthened by two observations: (i) types 4 and 6 can spread quickly if they enter efficient contact networks (36)(37)(38)(39) and (ii) in the absence of such networks, HCV type 1 in West Africa shows evidence of long-term endemic infection (7). However, the possibility of viral genetic variability in infectiousness among subtypes should not yet be discounted entirely (40). Extrapolating our estimates into the near future, it is clear that, in terms of new infections, subtype 1a poses the greatest threat to public health.…”
mentioning
confidence: 92%
“…This conclusion is strengthened by two observations: (i) types 4 and 6 can spread quickly if they enter efficient contact networks (36)(37)(38)(39) and (ii) in the absence of such networks, HCV type 1 in West Africa shows evidence of long-term endemic infection (7). However, the possibility of viral genetic variability in infectiousness among subtypes should not yet be discounted entirely (40). Extrapolating our estimates into the near future, it is clear that, in terms of new infections, subtype 1a poses the greatest threat to public health.…”
mentioning
confidence: 92%
“…Crucially, for HCV in Egypt it was possible to validate the genetic analysis against compelling epidemiological evidence (Frank et al, 2000). In addition to its epidemiological importance, HCV genetic diversity is of clinical relevance, as HCV genotypes vary in their susceptibility to treatment with ribavirin plus interferon (Yoshioka et al, 1992;Chemello et al, 1994;Zein, 2000) and in the effectiveness of the immune response that they elicit (Kimura et al, 2000). Furthermore, the enormous genetic diversity of HCV is a major obstacle to designing universally and sustainably efficacious vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…HCV variation could occur throughout the genome; indeed, the putative viral envelope glycoprotein gene shows unusually high degrees of amino acid variation. The envelope glycoprotein gene, especially HVR1, is a potential prime target for host humoral immunity [Mondelli et al, 1999] and contains neutralizing antigenic epitopes [Shang et al, 1999] that are clone-specific [Zhou et al, 1999;Kimura et al, 2000]. Research has showed that anti-E2 correlates with self-limited and chronic infection of HCV [Prince et al, 1999].…”
Section: Introductionmentioning
confidence: 99%